Amblypygi (Arachnida) occurrence in a protected area from the Brazilian Cerrado - Gabriel de Castro Jacques (Revista Chilena de Entomología)
The order Amblypygi represents just 0.1% of arachnid diversity, with 22 species recorded in Brazil. This number has increased especially in the first decades of the 21st century, despite the still conflicting detailed taxonomic description and the few distribution studies in the country. This justifies new studies to assess their occurrence, especially in hotspots such as the Cerrado biome. Therefore, this study aimed to reveal the Amblypygi fauna in the Cerrado areas of the Grande Sertão Veredas National Park. Collections took place between September 2022 and March 2023, through active search. Altogether, six specimens were recorded: one of Heterophrynus cheiracanthus (Gervais, 1842) and five of Heterophrynus sp., a result that expands the geographical distribution of H. cheiracanthus, hitherto unpublished for southeastern Brazil, and reaffirms the importance of the Grande Sertão Veredas National Park in protecting natural resources and biodiversity.